Synthesis and Characterization of Ammonium Potassium Tellurium Polyoxomolybdate: (NH4)2K2TeMo6O22·2H2O with One-Dimensional Anionic Polymeric Chain [TeMo6O22]4− - Lei Geng; Yunjian Wang (Crystals, 2021)
A new tellurium polyoxomolybdate hydrate (NH4)2K2TeMo6O22·2H2O was synthesized via the hydrothermal reaction method at 190 °C. The compound crystallizes in a one-dimensional tellurium polymolybdate [TeMo6O22]4− chain structure. The anionic polymeric chain is composed of Mo6O22 hexamers bridged together through sharing four corner oxygen atoms on the electron lone-paired TeO4 group. The Mo6O22 hexamer cluster is assembled from six distorted MoO6 octahedra in an edge-sharing manner. The ammonium and potassium cations distribute around the [TeMo6O22]4− chains and separate them from each other and maintain the charge balance. The thermal stability and optical properties of the compound were also investigated. The optical absorption data reveal that the compound is a wide band semiconductor with an optical band gap of 3.4 eV.